AMORIM, Henrique; SILVA, Jair Batista da. Classes e lutas de classes: novos questionamentos. São Paulo: Annablume, 2015. 250p. - de Oliveira Gerônimo, André (Caderno CRH, 2017)
http://dx.doi.org/10.1590/S0103-49792016000200016